2013
DOI: 10.1080/00036846.2012.714073
|View full text |Cite
|
Sign up to set email alerts
|

Economic uncertainty and corruption: evidence from a large cross-country data set

Abstract: A vast amount of research has considered numerous causes and correlates of corruption. Also, there have been many studies of the consequences of various forms of uncertainty. However, exploration of the nexus between economic uncertainty and corruption appears scarce. After providing an intuitive and heuristic linkage between general economic uncertainty and corruption, this article uses a large cross-country data set to augment a fairly standard model with simple proxies for uncertainty and to investigate how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 25 publications
4
15
0
Order By: Relevance
“…Treisman (2000) and Paldam (2001Paldam ( , 2002 found that corruption is a povertydriven disease which vanishes when the country becomes richer. Goel and Ram (2013) substantiated these findings and documented that transition economies have more corruption than developed countries. Gundlach and Paldam (2009) pointed out that the cross-country pattern of corruption can be fully explained by the cross-country pattern of income, and De Rosa et al (2010) found a strong correlation of 0.81 between GDP and the level of corruption.…”
Section: Incomesupporting
confidence: 60%
“…Treisman (2000) and Paldam (2001Paldam ( , 2002 found that corruption is a povertydriven disease which vanishes when the country becomes richer. Goel and Ram (2013) substantiated these findings and documented that transition economies have more corruption than developed countries. Gundlach and Paldam (2009) pointed out that the cross-country pattern of corruption can be fully explained by the cross-country pattern of income, and De Rosa et al (2010) found a strong correlation of 0.81 between GDP and the level of corruption.…”
Section: Incomesupporting
confidence: 60%
“…Furthermore, most of the studies conclude that, in general, women are less corrupt than man (Rivas 2012;Torgler & Valev 2010). From a macroeconomic point of view, inflation, economic development, economic freedom, income distribution (Ata & Arvas, 2011) as well as economic uncertainty (Goel and Ram, 2013) seem to be significantly related to corruption. Moreover, Rehman & Naveed (2007) found that GDP per capita, the unemployment rate, public expenditure and secondary school enrolments are significant factors influencing the level of corruption in a country.…”
Section: Introductionmentioning
confidence: 99%
“…There is empirical evidence corroborating how corruption has a significant effect on income uncertainty. For example, based on a cross-country data, Evrensel (2010) finds that higher corruption incidence increases growth volatility, whereas Goel and Ram (2013) argue that economic uncertainty has a positive association with corruption. Campos, Lien, and Pradhan (1999) studying firm survey data have established that the predictability of corruption can have a comparable effect on the investment decision to that of a lower incidence of corruption.…”
Section: Introductionmentioning
confidence: 99%